USE OF ADVANCED PEDAGOGICAL TECHNOLOGIES IN TEACHING ENGLISH - Khursanova Mokhinur Abdukahhor kizi (Galaxy International Interdisciplinary Research Journal, 2022)
As the world becomes ever more connected, the appeal of learning a new language is clear. Whether for business or pleasure, being able to communicate on an international level can bring many benefits. Nowadays most students of higher education want to use effective study methods so they can learn a language fast and speak it. So today English teachers of higher educations should be creative, searchable and find the best suitable method for each group or even for each student.In this article there are given some modern methods of teaching English.